A constituição de si : investigação otobiográfica com formadores de professores - Campos, Lídia Soares de (2012)
This research is a study conducted in the Graduate Program in Education at the Federal University of Mato Grosso, it is aligned to the philosophy of education area. It operates philosophical concepts from the readings, held held at GEDFFE - Studies and Research Group in Philosophy, Didactic and Teacher Education. Study about formation and who are in charge of it – the former teachers – as it is expressed in the job title, refers a priori to a big number of training spaces. My endowment is in a specific training area at UFMT: the Institute of Education (IE) that, among other courses, by teaching Pedagogy it has its greatest commitment. For this, I am closer to a post-structuralist approach that proposes to abandon the character of the prioritization of the object in search of knowledge, and that is based upon the subjectivist conceptions. I invest in authors as Nietzsche, Derrida and Deleuze as my precursors for discussion and to support the methodological approach of this research. Deconstructing is taken as reference. An otobiographical study enables one to use a method that opens and bursts, since the movement of understanding, based on the speaker, when adopting this way, we have a character of perspectivist. Therefore, I present an elaboration of the author thoughts and teachers in conversation. The aim is to investigate how these teachers became former teachers. For this, I based on Nietzsche, by taking the comprehension of experiences and the thesis that all text is a confession of its own author. From Derrida is borrowed the concept of otobiography, signature and academic freedom; Deleuze provides a discussion of the man expressions through the instincts and institutions such as procedures of satisfaction, I operate with Monteiro, the design of otobiography as a method of Research in Education Field, recreated by him as an otobiográfico method. The proposal of an otobiographical study is to hear the experiences and by listening attentively to them, it identifies the impulses that make the word in their speech and give meaning to people’s actions. In this research, basing myself on some assumptions: a) The Institute of Education consists in training professionals to work in public schools, as shown in the Pedagogical Political Project, b) We do not see the curriculum proposals aiming at the student’s integration in scientific projects, Masters or PhD, however, while hearing four former teachers’ lives they have showed me the opposite; c) there is a will that prevails in many of the former-teachers and less in the document that rules the course itself; d) instincts can satistafy their wills somehow and the Institute of Education is an artificial mean of satisfaction, designed to meet the needs of the instincts and theirs tendencies.